Golgi stress mediates redox imbalance and ferroptosis in human cells - Alborzinia, Hamed; Ignashkova, Tatiana I.; Dejure, Francesca Romana; Gendarme, Mathieu; Theobald, Jannick; Wölfl, Stefan; Lindemann, Ralph K.; Reiling, Jan H. (Communications biology, 2018)
Hamed Alborzinia et al. show that Golgi-dispersing compounds trigger iron-dependent oxidative degradation of lipids, inducing a non-apoptotic cell death called ferroptosis. This study provides insight into the role of Golgi apparatus for preventing ferroptotic cell death through its cellular redox control.
Gesehen am 30.04.2020